2004
DOI: 10.1097/00024382-200404000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation From Septic Shock With Capillary Leakage: Hydroxyethyl Starch (130 Kd), but Not Ringer’s Solution Maintains Plasma Volume and Systemic Oxygenation

Abstract: There is evidence suggesting that early fluid resuscitation is beneficial in the treatment of septic shock. The question as to which solution should be used remains controversial. Using a porcine septic shock model, we tested the effects of a new synthetic colloid hydroxyethyl starch (HES 130 kD) and a crystalloid regimen with Ringer's solution (RS) on plasma volume (PV) maintenance as well as on systemic and regional hemodynamics. Fourteen anaesthetized mechanically ventilated pigs received 0.75 g kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…HES solutions have been shown to attenuate the acute inflammatory response [18][19][20][21] , mitigate endothelial barrier dysfunction and vascular leak [18,22] , and preserve intestinal barrier function [17] . Small clinical trials have suggested superiority of HES solutions for resuscitation of the microcirculation in sepsis [22] .…”
Section: Type Of Fluid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…HES solutions have been shown to attenuate the acute inflammatory response [18][19][20][21] , mitigate endothelial barrier dysfunction and vascular leak [18,22] , and preserve intestinal barrier function [17] . Small clinical trials have suggested superiority of HES solutions for resuscitation of the microcirculation in sepsis [22] .…”
Section: Type Of Fluid Therapymentioning
confidence: 99%
“…HES solutions have been shown to attenuate the acute inflammatory response [18][19][20][21] , mitigate endothelial barrier dysfunction and vascular leak [18,22] , and preserve intestinal barrier function [17] . Small clinical trials have suggested superiority of HES solutions for resuscitation of the microcirculation in sepsis [22] . Small randomized clinical trials have also shown that early fluid resuscitation with HES solutions results in more rapid hemodynamic stabilization and shock reversal (i.e., greater efficacy) compared with crystalloids, and require significantly less fluid to restore intravascular volume [23,24] .…”
Section: Type Of Fluid Therapymentioning
confidence: 99%
“…1 Current state of the literature and study relevance Numerous experimental studies have provided a physiological rationale for the preferential use of a colloid over crystalloid therapy, with an emphasis on HES for resuscitation in septic shock and in states of acute stress (i.e., major trauma, perioperative). Hydroxyethyl starch solutions have been shown to attenuate the acute inflammatory response, 4-6 mitigate endothelial barrier dysfunction and vascular leak, 6,7 and preserve intestinal barrier function. 4 Small clinical trials have suggested HES solutions are also superior for resuscitation of the microcirculation in sepsis, 8 contribute to more rapid hemodynamic stabilization and shock reversal, and require significantly less fluid to restore intravascular volume.…”
Section: Commentarymentioning
confidence: 99%
“…1. Levels of plasma volume (PV) at baseline, and 6 h after induction of experimental sepsis in pigs [29]. RS: Ringer's solution; HES 130 kDa: 6 % hydroxyethyl starch 130/0.4.…”
Section: Fluid Resuscitation In Experimental Sepsismentioning
confidence: 99%
“…Using our porcine septic shock model, we tested the effects of HES 130 kDa and a crystalloid regimen with Ringer's solution on plasma volume maintenance as well as on systemic hemodynamics [29]. We found that it was possible in the presence of marked capillary leakage not only to maintain plasma volume and COP by HES 130 kDa but also as a consequence to preserve systemic oxygenation and hemodynamics ( Fig.…”
Section: Fluid Resuscitation In Experimental Sepsismentioning
confidence: 99%